Enhancing the Competitiveness of MSMEs in the Economic Development of West Sumatra Through Android-based Approaches: A Review under Ministerial Regulation No. 55 of 2022 - Yonna Anggayu Putri; Harmelia Harmelia; Mutia Seplinda (International Journal of Economics Development Research (IJEDR), 2024)
The research's objective is to create an Android-based application that documents monthly transactions for MSMEs and develops a calculator for calculating MSMEs final income tax in compliance with the standards outlined in Government Regulation No. 55 of 2022. The research population comprises 50 MSMEs in Padang City registered with the Department of MSMEs in Padang, Data sources were gathered from various references, including financial reports of MSMEs, final income tax calculations for MSMEs, and literature related to software engineering and mobile application programming, System testing was conducted using Black Box Testing. The Android-based policy of Government Regulation Number 55 of 2022 has a partial effect on the development of MSME taxpayers. Trust in the government partially influences the development of MSME taxpayers. The Android application for final income tax calculation for MSMEs, based on Government Regulation No. 55 of 2022, has been implemented. MSMEs can use it in recapping business income and calculating Final Income Tax in accordance with tax regulations. Testing shows 100% compliant functionality. Government Policy No. 55 of 2022 based on Android explains that the dependent variable for the development of MSME taxpayers is 55.1%. The ease of calculating MSME taxes allows them to compete in West Sumatra and focus on marketing strategies.